Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Bernreuther, Marco; Dellnitz, Michael; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Sonntag, Konstantin; Volkwein, Stefan (arXiv:2308.01113)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control - potentially with non-smoothness both on the level of the objectives or in the system dynamics. This results in new challenges such as dealing with expensive models (e.g., governed by partial differential equations (PDEs)) and developing dedicated algorithms handling the non-smoothness. Since in contrast to single-objective optimization, the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in the field of multiobjective optimization of non-smooth PDE-constrained problems. In particular we report on the advances achieved within Project 2 "Multiobjective Optimization of Non-Smooth PDE-Constrained Problems - Switches, State Constraints and Model Order Reduction" of the DFG Priority Programm 1962 "Non-smooth and Complementarity-based Distributed Parameter Systems: Simulation and Hierarchical Optimization".

Gelingensbedingungen für den Einsatz digitaler Medien in Lernsituationen in der Grundschule im Bereich Lesen – Befunde einer qualitativen Befragung von Lehrpersonen - Lorenz, R.; Brüggemann, T. U.; Eickelmann, Birgit; McElvany, N. (Jahrbuch für Schulentwicklung)

Neuartige Flugstrom SCR an online synthetisierten, nanoskaligen Katalysatorpartikeln in einem kombinierten Gasreinigungsprozess (Poster) - Beimdiek, Janis; Schiller, Sascha; Schmid, Hans-Joachim

Investigations on Aerosol Synthesis of Polymer Particles - Elma, Benjamin; Beimdiek, Janis

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Curriculare Überlegungen zum fach- und berufsorientierten Deutsch - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Curriculumkompetenz - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

DaF-Übungsfirma - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Globale Simulation - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Fallstudie - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

Planspiel - Prikoszovits, Matthias (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis)

DaF und DaZ im Kontext Deutsch für den Beruf: Schnittstellen und Divergenzen - Niederhaus, Constanze; Prikoszovits, Matthias (Deutsch als Fremdsprache)

"DAS iSt STRASSEN-PoLiTiK!" Politisches "meaning making" im Szene-Graffiti - Tophinke, Doris (Kunst und Politik)

From mental models to algorithmic imaginaries to co-constructive mental models - Schulz, Christian (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Tech/Imaginations – Introduction - Schulz, Christian; Schröter, Jens (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Tech/Imaginations (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften)

Infrastrukturen der Anerkennung. Eine Theorie sozialer Medienplattformen - Schulz, Christian

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Investigation of the Deposition Velocity Related Temperature Deviations for High Temperature Materials in the FDM Process - Moritzer, Elmar; Hecker, Felix; Knaup, Felix; Wächter, Julian (Proceedings of the 37th International Conference of the Polymer Processing Society (PPS-37))

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusion in den Erziehungshilfen III – Kinderschutz inklusiv gedacht)

Geschlechter - Verhältnisse - Widersprüche. Eine Einleitung - Hoffarth, Britta; Mentzing, Stina; Richter, Susanne (Geschlechter - Verhältnisse - Widersprüche)

Multiple Verhandlungen: ›Cancel Culture‹ aus Perspektive feministischer Digitalisierungsforschung - Richter, Susanne (Geschlechter - Verhältnisse - Widersprüche)

Geschlechter - Verhältnisse - Widersprüche

Cancel Culture als Arena politisierter Wissenskonflikte Am Beispiel einer Debatte um rassistische Begriffe im Sommer 2022 - Richter, Susanne (Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Das UNESCO-Welterbe und seine Akteur:innen. Identifikation – Nominierung – Evaluierung – Etablierung - Seng, Eva- Maria (Kulturen)

Socialist AI? Societal Use, Economic Implementation, and the Tensions of Applied Computer Science in Late Socialist GDR - Schmitt, Martin (IEEE Annals of the History of Computing)
Keywords: Sozialismus; Schachcomputer; Deutschland {<}DDR{>}; KI; Schach; Spätsozialismus; 1980er-Jahre

Umweltgeschichte der Digitalisierung in der DDR - Schmitt, Martin (Umweltgeschichte)
(An environmental history of computing of the GDR) Since 1960, the SED has pursued a forced digitization of the state. The goal was to increase the efficiency of the economy. Contrary to the common perception of the GDR as technically backward, it succeeded in building up a powerful IT industry and using computers in many areas. However, the venture was not without risks. In addition to technical failures of the computer systems, the supposedly environmentally friendly information technology posed a danger to the environment and health. Especially in the production of silicon for computer chips, numerous accidents occurred, resulting in health problems and fatalities. Therefore, even the inhabitants of Dresden protested against the settlement of a high-purity silicon plant and thus against the regime at the end of the 1980s. 11 sources will explore the background, connections and social debates surrounding the consequences of digitalization in the GDR. German: Die SED verfolgte seit 1960 eine forcierte Digitalisierung des Staates . Ziel war es, die Effizienz der Wirtschaft zu steigern . Entgegen der geläufigen Wahrnehmung der DDR als technisch rückständig gelang es ihr, eine leistungsfähige IT- Industrie aufzubauen und Computer in vielen Bereichen einzusetzen . Das Unterfangen blieb aber nicht ohne Risiken. Neben technischen Ausfällen der Computersysteme konnte die vermeintlich umweltfreundliche Informationstechnik zur Gefahr für Umwelt und Gesundheit werden. Vor allem in der Siliziumproduktion für Computerchips kam es zu zahlreichen Unfällen mit Gesundheitsschäden und Toten. Ende der 1980er-Jahre protestierten daher sogar die Einwohner Dresdens gegen die Ansiedlung eines Reinstsiliziumwerkes und damit gegen das Regime. In 11 Quellen werden die Grundlagen, Zusammenhänge und gesellschaftlichen Debatten der Digitalisierung in der DDR und ihren Folgen diskutiert.

Von der Region in die Republik? Die Bedeutung der Region in der Frühphase der Digitalisierung in Deutschland am Beispiel der DDR-Finanzorgane - Schmitt, Martin (Varianten des Wandels. Neue Perspektiven auf die Region in der jüngsten Zeitgeschichte, 1970-2020)

A new algorithmic imaginary - Schulz, Christian (Media, Culture & Society)
The algorithmic imaginary as a theoretical concept has received increasing attention in recent years as it aims at users’ appropriation of algorithmic processes operating in opacity. But the concept originally only starts from the users’ point of view, while the processes on the platforms’ side are largely left out. In contrast, this paper argues that what is true for users is also valid for algorithmic processes and the designers behind. On the one hand, the algorithm imagines users’ future behavior via machine learning, which is supposed to predict all their future actions. On the other hand, the designers anticipate different actions that could potentially performed by users with every new implementation of features such as social media feeds. In order to bring into view this permanently reciprocal interplay coupled to the imaginary, in which not only the users are involved, I will argue for a more comprehensive and theoretically precise algorithmic imaginary referring to the theory of Cornelius Castoriadis. In such a perspective, an important contribution can be formulated for a theory of social media platforms that goes beyond praxeocentrism or structural determinism.
Keywords: Sociology and Political Science; Communication

Probabilistic Scoring Lists for Interpretable Machine Learning - Hanselle, Jonas Manuel; Fürnkranz, Johannes; Hüllermeier, Eyke (26th International Conference on Discovery Science)

Towards Interpretability in Audio and Visual Affective Machine Learning: A Review - Johnson, David; Hakobyan, Olya; Drimalla, Hanna
Machine learning is frequently used in affective computing, but presents challenges due the opacity of state-of-the-art machine learning methods. Because of the impact affective machine learning systems may have on an individual's life, it is important that models be made transparent to detect and mitigate biased decision making. In this regard, affective machine learning could benefit from the recent advancements in explainable artificial intelligence (XAI) research. We perform a structured literature review to examine the use of interpretability in the context of affective machine learning. We focus on studies using audio, visual, or audiovisual data for model training and identified 29 research articles. Our findings show an emergence of the use of interpretability methods in the last five years. However, their use is currently limited regarding the range of methods used, the depth of evaluations, and the consideration of use-cases. We outline the main gaps in the research and provide recommendations for researchers that aim to implement interpretable methods for affective machine learning.

EEG Correlates of Distractions and Hesitations in Human–Robot Interaction: A LabLinking Pilot Study - Richter, Birte; Putze, Felix; Ivucic, Gabriel; Brandt, Mara; Schütze, Christian; Reisenhofer, Rafael; Wrede, Britta; Schultz, Tanja (Multimodal Technologies and Interaction)
In this paper, we investigate the effect of distractions and hesitations as a scaffolding strategy. Recent research points to the potential beneficial effects of a speaker’s hesitations on the listeners’ comprehension of utterances, although results from studies on this issue indicate that humans do not make strategic use of them. The role of hesitations and their communicative function in human-human interaction is a much-discussed topic in current research. To better understand the underlying cognitive processes, we developed a human–robot interaction (HRI) setup that allows the measurement of the electroencephalogram (EEG) signals of a human participant while interacting with a robot. We thereby address the research question of whether we find effects on single-trial EEG based on the distraction and the corresponding robot’s hesitation scaffolding strategy. To carry out the experiments, we leverage our LabLinking method, which enables interdisciplinary joint research between remote labs. This study could not have been conducted without LabLinking, as the two involved labs needed to combine their individual expertise and equipment to achieve the goal together. The results of our study indicate that the EEG correlates in the distracted condition are different from the baseline condition without distractions. Furthermore, we could differentiate the EEG correlates of distraction with and without a hesitation scaffolding strategy. This proof-of-concept study shows that LabLinking makes it possible to conduct collaborative HRI studies in remote laboratories and lays the first foundation for more in-depth research into robotic scaffolding strategies.
Keywords: Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Neuroscience (miscellaneous)

SNAPE: A Sequential Non-Stationary Decision Process Model for Adaptive Explanation Generation - Robrecht, Amelie; Kopp, Stefan (Proceedings of the 15th International Conference on Agents and Artificial Intelligence)

Technical Transparency for Robot Navigation Through AR Visualizations - Dyck, Leonie; Beierling, Helen; Helmert, Robin; Vollmer, Anna-Lisa (Companion of the 2023 ACM/IEEE International Conference on Human-Robot Interaction)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

Norms and Rituals of Conflict Settlement in Foreign Affairs in the High Middle Ages - Kamp, Hermann (Le Mediaeval Journal)

Edirom/WeGA-ODD: WeGA ODD files release 4.7.0 - Stadler, Peter; Anna Maria, Neubert; Schreiter, Solveig; Obert, Salome; Ried, Dennis

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert (forschung - Das Magazin der Deutschen Forschungsgemeinschaft)

Gesundheitsmanagement: Gesunde Mitarbeiter - gesunder Betrieb? - Meier, Heiko; Sennefelder, Lisa (markt&wirtschaft)

Sportliche Angebote zur Förderung von Vertrauen in öffentlichen Verwaltungen - Sennefelder, Lisa

Pushing the Limits of Computational Combinatorial Constructions (Dagstuhl Seminar 23161) - Moura, Lucia; Nakic, Anamari; Östergård, Patric; Wassermann, Alfred; Weiß, Charlene
This report documents the program and the outcomes of Dagstuhl Seminar 23161 "Pushing the Limits of Computational Combinatorial Constructions". In this Dagstuhl Seminar, we focused on computational methods for challenging problems in combinatorial construction. This includes algorithms for construction of combinatorial objects with prescribed symmetry, for isomorph-free exhaustive generation, and for combinatorial search. Examples of specific algorithmic techniques are tactical decomposition, the Kramer-Mesner method, algebraic methods, graph isomorphism software, isomorph-free generation, clique-finding methods, heuristic search, SAT solvers, and combinatorial optimization. There was an emphasis on problems involving graphs, designs and codes, also including topics in related fields such as finite geometry, graph decomposition, Hadamard matrices, Latin squares, and q-analogs of designs and codes.
Keywords: automorphism groups; combinatorial algorithms; finite geometries; subspace designs

Geschichte heilen: Urbane Interventionen und ihre Deutung durch den päpstlichen Hofarchitekten Domenico Fontana (1543–1607) - Voß, Fabian (Antike und Abendland)

»Play it again, Sam« – Levels of Complexity in Encoding Performance Personnel - Bohl, Benjamin W.; Ried, Dennis (Music Encoding Conference Proceedings 2022)

Ludwig Baumann - Ried, Dennis (Blick in die Geschichte. Karlsruher stadthistorische Beiträge)

HenDi-ODD v2.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v1.0.0 - Ried, Dennis

HenDi-ODD v1.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v2.0.0 - Ried, Dennis

Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

Entrained flow SCR using an in-situ synthesis of catalyst particles for a combined flue gas cleaning system - Beimdiek, Janis; Schiller, Sascha; Schmid, Hans-Joachim

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Meier, Torsten

“Sorry, Too Much Information”. Designing Online Review Systems that Support Information Search and Processing - Seutter, Janina; Kutzner, K.; Stadtländer, M.; Kundisch, Dennis; Knackstedt, R. (Electronic Markets)

Verdrängen Smart-Product-Service-Systeme die Interaktion in Online-Communities? – Empirische Evidenz aus einer Rezept-Community - Seutter, Janina; Müller, Michelle; Kundisch, Dennis (Wirtschaftsinformatik & Management)

Speech Disentanglement for Analysis and Modification of Acoustic and Perceptual Speaker Characteristics - Rautenberg, Frederik; Kuhlmann, Michael; Ebbers, Janek; Wiechmann, Jana; Seebauer, Fritz; Wagner, Petra; Haeb-Umbach, Reinhold (Fortschritte der Akustik - DAGA 2023)

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (Lernen, Wissen, Daten, Analysen (LWDA) Conference Proceedings)
The selection of useful, informative, and meaningful features is a key prerequisite for the successful application of machine learning in practice, especially in knowledge-intense domains like decision support. Here, the task of feature selection, or ranking features by importance, can, in principle, be solved automatically in a data-driven way but also supported by expert knowledge. Besides, one may of course, conceive a combined approach, in which a learning algorithm closely interacts with a human expert. In any case, finding an optimal approach requires a basic understanding of human capabilities in judging the importance of features compared to those of a learning algorithm. Hereto, we conducted a case study in the medical domain, comparing feature rankings based on human judgment to rankings automatically derived from data. The quality of a ranking is determined by the performance of a decision list processing features in the order specified by the ranking, more specifically by so-called probabilistic scoring systems.

A micropolar model accounting for asymmetric behavior of cold‐box sand in relation to tensile and compression tests - Börger, Alexander; Mahnken, Rolf (PAMM)
Abstract Cold‐box sand (CBS) belongs to the granular materials and consists of sand and a binder. The behavior of CBS is simulated with a micropolar model, whereby the additional degree of freedom of the model describes the rotation of the sand grains. The model is used to generate a shear band under pressure for three different meshes, where the force‐displacement curves of the three meshes converge so that no mesh dependence occurs. Another requirement of the model is the consideration of asymmetric behavior for compression and tension. Due to the additional degree of freedom the implicit implementation of the micropolar continuum is very time‐consuming. Therefore, an explicit implementation is considered as an alternative possibility. This paper compares the advantages and disadvantages of both methods and the results for both calculations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Static Analysis for Android GDPR Compliance Assurance - Khedkar, Mugdha (Proceedings of the 45th International Conference on Software Engineering: Companion Proceedings (ICSE ‘23))
Many Android applications collect data from users. When they do, they must protect this collected data according to the current legal frameworks. Such data protection has become even more important since the European Union rolled out the General Data Protection Regulation (GDPR). App developers have limited tool support to reason about data protection throughout their app development process. Although many Android applications state a privacy policy, privacy policy compliance checks are currently manual, expensive, and prone to error. One of the major challenges in privacy audits is the significant gap between legal privacy statements (in English text) and technical measures that Android apps use to protect their user's privacy. In this thesis, we will explore to what extent we can use static analysis to answer important questions regarding data protection. Our main goal is to design a tool based approach that aids app developers and auditors in ensuring data protection in Android applications, based on automated static program analysis.
Keywords: static analysis; data protection and privacy; GDPR compliance

Migrationsbedingte Vielfalt und Diversität auf Kinderseiten. Eine Auseinandersetzung mit Medienangeboten auf KiKa in kultursensitiver Perspektive - Günesli, Habib (Bildung, Diversität und Medien. Erkundungen entlang aktueller Diskurslinien. Festschrift für Gudrun Marci-Boehncke)
Der Beitrag setzt sich vor dem Hintergrund von interkultureller und kultursensitiver (Früh-)Pädagogik mit Diversität und migrationsbedingter Vielfalt im Programm des KIKA auseinander. Beispielhaft untersucht wird hier die Comedy Moooment! Es wird die Bedeutung einer gelungenen Medienpädagogik, die (migrationsbedingte) Diversität sowie Vielfalt berücksichtigt und Kultursensitivität fördert, betont.
Keywords: Mehrsprachigkeit; Migration; Medien; Frühe Kindheit; Diversität; Vielfalt

Positionierung zum Moratorium der Digitalisierung in Kitas und Schulen. Von der Notwendigkeit einer fachlichen Einordnung aus Sicht der GMK e.V. (Schule und Digitalisierung – Neue Lernformate für die Zukunft)
Keywords: Moratorium; Medienbildung; Frühe Bildung; Digitalisierung; Jugendmedienschutz; Medienkompetenz; Prävention; Professionalisierung

Discourse traditions, text linguistics, and translation studies - Albrecht, Jörn; Kunert, Irene Dorothea (Manual of Discourse Traditions in Romance)

Felix Tacke, Sprachliche Aufmerksamkeitslenkung. Historische Syntax und Pragmatik romanischer Zeigeaktkonstruktionen, Frankfurt am Main (Vittorio Klostermann) 2022, xiii + 616 p. (Analecta Romanica 92) - Kunert, Irene Dorothea (Vox Romanica)

Präferenzen beim Gebrauch von Konklusionsmarkern im Französischen und im Deutschen - Kunert, Irene Dorothea (Comparatio delectat IV (vorläufiger Titel; Artikel eingereicht 2023))

Nächtliche sympathische Aktivität und subjektive Symptome nach sport-assoziierter Concussion: eine Pilotstudie - Delling, Anne Carina; Jakobsmeyer, Rasmus; Christiansen, Nele; Coenen, Jessica; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Eine sport-assoziierte Concussion (saC) ist eine oftmals unterschätzte Hirnverletzung, die vor allem in Kontakt- und Kollisionssportarten häufig vorkommt. SaCs können zu einer Vielzahl an klinischen Symptomen führen. Akute und zum Teil die klinische Regeneration überdauernde parasympathische Inhibierung im Autonomen Nervensystem (ANS) wurde nach saC bereits häufig beschrieben. Über Veränderungen im sympathischen Nervensystem ist jedoch noch wenig bekannt. Diese wurden durch Messungen der elektrodermalen Aktivität (EDA) im Schlaf, der erheblich zur Regeneration nach saC beiträgt, sowie im Zusammenhang mit subjektiven Symptomen nach saC im Rahmen einer Pilotstudie untersucht. Methode 18 Sportler und Sportlerinnen mit diagnostizierter saC und 18 nach Alter, Geschlecht, Größe, Gewicht, Sportart und Leistungsklasse gematchte Kontrollathleten und -athletinnen trugen in den Nächten während der individuellen Return-to-Sport (RTS) Phase sowie drei Wochen nach Abschluss des RTS (postRTS) einen Handgelenkssensor (E4 Empatica Inc., Mailand, Italien). Anteile nächtlicher tonischer (meanEDA) und phasischer (EDRs, Schlafstürme) EDA wurden zwecks Gruppenvergleich ermittelt und mit saC-Symptomen (SCAT5) sowie dem subjektiven Erholungszustand nach Schlaf mittels Mann-Whitney U-Tests oder ungepaarten t-Tests verglichen. Ergebnisse Während und nach dem RTS konnten keine Gruppenunterschiede in den nächtlichen EDA-Parametern nachgewiesen werden. Eine höhere meanEDA während des RTS korrelierte mit einer höheren Anzahl an Symptomen (p=0,025, r=0,525) und eine erhöhte phasische EDA mit einem geringeren Anstieg des subjektiven Erholungszustands von vor zu nach Schlaf (EDRs: p=0,007, r=−0,642; EDRs/min: p>0,001, r=−0,762; Schlafstürme: p=0,011, r=−0,616). Fazit Die nächtliche EDA nach saC unterschied sich während und nach dem RTS nicht signifikant zu gematchten Kontrollsportlern und -sportlerinnen. Der Zusammenhang zwischen höherer EDA während des RTS und der Anzahl an saC-Symptomen sowie der geringeren subjektiven Erholung nach Schlaf könnte sowohl ursächlich für als auch Effekt der subjektiven Symptome sein und sollte durch Baseline-Messungen und in Kombination mit parasympathischen Markern künftig weiter untersucht werden.
Keywords: General Medicine

Large Scale Scanning of TLS Session Ticket Confusion - Storm, Tim Leonhard
Session tickets are a resumption mechanism, which can speed up repeated TLS connections. To do so, information is stored client-side, encrypted with an additional symmetric key, which is separate from existing private keys. A server only has to store this key, making session tickets stateless for the server. If the key is shared between servers, a client can be misled into resuming a session with a different, less secure server. In this thesis, we design and implement a scan for detecting prerequisites to such an attack, by requesting and redeeming tickets for pair-wise servers. We find that 17,901 out of 22,127 scanned (virtual) hosts are potentially vulnerable to this attack because they share their keys and accept tickets issued for other domains. We discuss the difficulties of detecting such an attack and show that unfortunately, our approach does not scale to larger sample sizes.

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Communications in Computer and Information Science)

Rezension zu: Bette, K.-H. & Kühnle, F.: Flitzer im Sport – Zur Sozialfigur des Störenfrieds - Sennefelder, Lisa (Sport und Gesellschaft)

Self-Stabilizing Skip-Graph with Growth-bounded Metric - Beckendorf, Björn

khiṭāb al-karāhiya – iṭlāla ʿala taʾwīlāt maghlūṭa li-n-nuṣūṣ al-islāmiya (Hassrede – Überblick auf kritische Interpretationen islamischer Texte) - Abdelrahem, Mohammed (khiṭāb al-karāhiya wa-taḥaddiyāt al-ḥiwār – taqāṭuʿāt wa-muwāǧahāt (Hassrede und die Herausforderungen des Dialogs – Überschneidungen und Konfrontationen))
Keywords: Dialog der Religionen; interreligiöser Dialog; Hass; Hassrede

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (ESANN 2023 proceedings)

SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (NeurIPS 2023 - Advances in Neural Information Processing Systems)

LitCQD: Multi-Hop Reasoning in Incomplete Knowledge Graphs with Numeric Literals - Demir, Caglar; Wiebesiek, Michel; Lu, Renzhong; Ngonga Ngomo, Axel-Cyrille; Heindorf, Stefan (ECML PKDD)

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Inorganic Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐RuII complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Analytical Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (International Conference on Industry Sciences and Computer Science Innovation)

Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Towards a Data-Driven Product Management – Concepts, Advantages, and Future Research - Fichtler, Timm; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Megatrends, such as digitization or sustainability, are confronting the product management of manufacturing companies with a variety of challenges regarding the design of future products, but also the management of the actual products. To successfully position their products in the market, product managers need to gather and analyze comprehensive information about customers, developments in the products’ environment, product usage, and more. The digitization of all aspects of life is making data on these topics increasingly available – via social media, documents, or the internet of things from the products themselves. The systematic collection and analysis of these data enable the exploitation of new potentials for the adaption of existing products and the creation of the products of tomorrow. However, there are still no insights into the main concepts and cause-effect relationships in exploiting data-driven approaches for product management. Therefore, this paper aims to identify the main concepts and advantages of data-driven product management. To answer the corresponding research questions a comprehensive systematic literature review is conducted. From its results, a detailed description of the main concepts of data-driven product management is derived. Furthermore, a taxonomy for the advantages of data-driven product management is presented. The main concepts and the taxonomy allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.
Keywords: Product Lifecyle Management (PLM); Data Analytics; Data-driven Design; Engineering Management; Lifecycle Data

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

CFD-Untersuchungen der Fluiddynamik und des Wärmetransports an rauen Oberflächen - Hollenhorst, Viola; Kenig, Eugeny Y.

Modellierung der Reaktivabsorption in regellosen Schüttungen und modellbasierte Optimierung von Füllkörpern mit dem Ansatz der hydrodynamischen Analogien - Salten, Alexander Heinrich Johannes
Füllkörper spielen in industriellen Trennprozessen eine wichtige Rolle bspw. bei der Reinigung industrieller Abgase durch Absorption. Die Trennleistung von Füllkörperkolonnen wird üblicherweise mittels vereinfachter Stufenmodelle ermittelt, deren Modellparameter experimentell bestimmt werden müssen. Dies stellt eine große Schwäche von Stufenmodellen dar, da diese Parameterim Allgemeinen nicht auf verschiedene Stoffsysteme und Füllkörpertypen übertragbar sind.In dieser Arbeit wird ein Modell, basierend auf dem hydrodynamischen Analogieansatz, zur Beschreibung von Absorptionsvorgängen in Füllkörperkolonnen vorgestellt. Dabei ist die Geometrie der festen Phase direkt abhängig von der Füllkörpergeometrie und der Stochastik der Schüttung. Die tatsächlichen Strömungsverhältnisse in Füllkörperkolonnen werden erfasst und durch eine Kombination vereinfachter charakteristischer Strömungsformen reproduziert. Dies erlaubt die Verwendung rigoroser Transportgleichung. Dadurch enthält das Modell weniger experimentell zu ermittelnde Parameter und ist damit unabhängiger von Experimenten als vereinfachte Stufenmodelle. Das Modell wurde gegen experimentelle Daten zur CO2-Absorption in wässrige Natronlauge validiert. Mit dem entwickelten Modell wurde anschließend eine Parameterstudie durchgeführt, die der Unterstützung der Entwicklung neuer Füllkörpergeometrien dient. Dazu wurde eine Simulationsstudie durchgeführt, die den Einfluss der Füllkörpergeometrie auf die Trennleistung untersucht.

Einseitiges Widerstandselementschweißen für die stahlintensive Mischbauweise - Haak, Viktor; Meschut, Gerson; Epperlein, Maike; Schiebahn, Alexander; Reisgen, Uwe (25. DVS-Sondertagung Widerstandsschweißen)

Optimal scheduling of a large-scale power-to-ammonia process: Effects of parameter optimization on the indirect demand response potential - Hochhaus, Thorben; Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

Demand Side Management Implementation in Downstream Digestate Treatment of a Biomethane Biorefinery - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Chemical Engineering Transactions)

Decision support tool to determine the suitability of demand side management implementation in continuously operated processes – A biorefinery case study - Röder, Lilli; Etzold, Hendrik; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract The time‐dependent adjustment of a system's power demand simultaneously with current power generation is commonly referred to as demand side management (DSM). DSM strategies are based on the flexibility to purchase electricity at times when prices are low, which can result in monetary benefits. One option to increase the flexibility of continuously operated processes is to oversize them. From an economic point of view, this leads to an increased investment. DSM only serves an economic purpose if the monetary benefits exceed this increase in capital costs. The main goal of this contribution is to develop a decision support tool to help evaluate unit operations regarding their feasibility for DSM implementation. In a case study, the decision support tool was applied to show its functionality on a biomethane production plant. The results show that with the help of the decision support tool, evaluating unit operations concerning their economic DSM potential is possible.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

Intersektionalität und erzählte Welten – Einführung - Abrego, Verónica; Henke, Ina; Kißling, Magdalena; Lammer, Christina; Leuker, Maria-Th. (Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien)

Het verschil tussen strips en graphic novels (in Vlaanderen) - Lammer, Christina

Power-to-hydrogen and hydrogen-to-X energy systems for the industry of the future in Europe - Genovese, Matteo; Schlüter, Alexander; Scionti, Eugenio; Piraino, Francesco; Corigliano, Orlando; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)
Keywords: Hydrogen economy; Green hydrogen; Power-to-X; Hydrogen-to-X; Sector coupling

Pre-equilibrium photons from the early stages of heavy-ion collisions - Oscar Garcia-Montero, Oscar Garcia-Montero; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (arXiv:2308.09747)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity $η/s$ and entropy density $dS/dζ \sim {\scriptstyle \left(Tτ^{1/3}\right)^{3/2}}_∞$. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in $\sqrt{s_{NN}}=2.76\,\text{TeV}$ 0-20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.

Open Educational Resources in der beruflichen Bildungslandschaft - Schneider, Jennifer Nicole

Experimental Study of an Internally Channeled Tube Heat Exchanger under Turbulent Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

Numerical analysis of failure modeling in clinching process chain simulation - Bielak, Christian Roman; Böhnke, Max; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. The application of the mechanical joining process clinching allows the assembly of different sheet metal materials with a wide range of material thickness configurations, which is of interest for lightweight multi-material structures. In order to be able to predict the clinched joint properties as a function of the individual manufacturing steps, current studies focus on numerical modeling of the entire clinching process chain. It is essential to be able to take into account the influence of the joining process-induced damage on the load-bearing capacity of the joint during the loading phase. This study presents a numerical damage accumulation in the clinching process based on an implemented Hosford-Coulomb failure model using a 3D clinching process model applied on the aluminum alloy EN AW-6014 in temper T4. A correspondence of the experimentally determined failure location with the element of the highest numerically determined damage accumulation is shown. Moreover, the experimentally determined failure behavior is predicted to be in agreement in the numerical loading simulation with transferred pre-damage from the process simulation.

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.